2010
DOI: 10.1161/atvbaha.110.206680
|View full text |Cite
|
Sign up to set email alerts
|

Repressors NFI and NFY Participate in Organ-Specific Regulation of von Willebrand Factor Promoter Activity in Transgenic Mice

Abstract: Objective To determine the role of repressors in cell type and organ-specific activation of von Willebrand factor (VWF) promoter sequences −487 to +247 in vivo. Methods and Results Activation patterns of wild-type and mutant VWF promoters (sequences −487 to +247) containing mutations in repressors NFI- and NFY-binding sites were analyzed in transgenic mice. Mutation of the NFI-binding site activated the promoter in heart and lung endothelial cells, whereas mutation of the NFY-binding site activated the promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…This VWF mosaicism may be static (aorta) or dynamically regulated by transcriptional mechanisms involving the VWF promoter . For example, VWF is virtually undetectable within resting glomerular capillaries of mice but is inducible by inhibition of the repressor nuclear factor‐I . A patchy staining for VWF has been also reported in normal human kidney tissue and, in vitro, with primary glomerular EC (GEC) …”
Section: Are All Endothelial Cells Made Equal?mentioning
confidence: 99%
“…This VWF mosaicism may be static (aorta) or dynamically regulated by transcriptional mechanisms involving the VWF promoter . For example, VWF is virtually undetectable within resting glomerular capillaries of mice but is inducible by inhibition of the repressor nuclear factor‐I . A patchy staining for VWF has been also reported in normal human kidney tissue and, in vitro, with primary glomerular EC (GEC) …”
Section: Are All Endothelial Cells Made Equal?mentioning
confidence: 99%
“…VWF promoter activity is highly influenced by the interaction of a number of transacting factors that function as activators, repressors, or have a dual function (Fig. A) . To determine whether alterations observed in gene array analyses are also reflected by other gene expression analyses methods, we explored the expression pattern of the previously identified VWF regulatory transacting factors by RT‐PCR analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…in vivo analyses of the VWF promoter demonstrated that while the sequence −487 to +247 exhibited endothelial specificity, it was only sufficient for promoter activation in the brain , and additional regions were required for activation in other organs . Furthermore, in vivo mutational analyses of the VWF promoter transgene demonstrated that mutation in the NFI binding site leads to VWF promoter sequence −487 to +247‐driven gene expression in endothelial cells of lung and heart, whereas mutations in the repressor NFY binding site (+226 to +234) results in VWF promoter activation in kidney endothelial cells . These results demonstrate a clear role for the repressors NFI and NFY in organ‐specific regulation of the VWF promoter.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations